2016
DOI: 10.1038/srep21631
|View full text |Cite
|
Sign up to set email alerts
|

Individual Apostichopus japonicus fecal microbiome reveals a link with polyhydroxybutyrate producers in host growth gaps

Abstract: Gut microbiome shapes various aspects of a host’s physiology, but these functions in aquatic animal hosts have yet to be fully investigated. The sea cucumber Apostichopus japonicus Selenka is one such example. The large growth gap in their body size has delayed the development of intensive aquaculture, nevertheless the species is in urgent need of conservation. To understand possible contributions of the gut microbiome to its host’s growth, individual fecal microbiome comparisons were performed. High-throughpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(87 citation statements)
references
References 62 publications
5
82
0
Order By: Relevance
“…Rhodobacterales was more abundant in sea cucumbers treated with 15 g/kg JAP compared to the 10 g/kg JAP treatment (one‐way ANOVA, p < .05; Figure c), which was consistent with the differences in growth rate observed in these two treatment conditions. Previous studies have shown that the relative abundance of Rhodobacterales influences the growth rate of sea cucumbers (Yamazaki et al, ), and our results support this hypothesis. The relative abundance of Flavobacteriales was higher in the Control 2 group compared to the group treated with 15 g/kg JAP ( p < .05).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Rhodobacterales was more abundant in sea cucumbers treated with 15 g/kg JAP compared to the 10 g/kg JAP treatment (one‐way ANOVA, p < .05; Figure c), which was consistent with the differences in growth rate observed in these two treatment conditions. Previous studies have shown that the relative abundance of Rhodobacterales influences the growth rate of sea cucumbers (Yamazaki et al, ), and our results support this hypothesis. The relative abundance of Flavobacteriales was higher in the Control 2 group compared to the group treated with 15 g/kg JAP ( p < .05).…”
Section: Resultssupporting
confidence: 90%
“…Therefore, the relative abundance of Rhodobacterales may impact the growth rate of sea cucumbers. Similar results were observed in a previous study (Yamazaki et al, ). Our results also suggested that the supplementation of 15 g/kg of JAP significantly promoted the growth of the order Rhodobacterales in the gut microbiota while reducing the proportion of potentially harmful bacteria.…”
Section: Discussionsupporting
confidence: 93%
“…Bacterial community is not only an essential component of the gut, but also associated with the life stages such as immune regulation, metabolic absorption, etc (Ellegaard & Engel, 2016;Hegarty, Goopy, Herd & McDorkell, 2007;Yamazaki et al, 2016;Zhou, Hernandezsanabria & Guan, 2009). With a unique ability of gut regeneration, sea cucumber excretes its gut and the respiratory tree from its body via its mouth or cloaca when subjected to external stimulation, and completely regenerates a new digestive system within a very short period of time (Shukalyuk & Dolmatov, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…These enriched bacterial groups, Vibrionales, Alteromonadales and Rhodobacterales, have already been proposed as probiotics candidates positively affecting physiology of A . japonicus in previous study (Chi et al ., ; Yamazaki et al ., ). Additionally, Flavobacteriales could also be a new target for probiotics in sea cucumbers.…”
Section: Resultsmentioning
confidence: 97%
“…Characterizing sea cucumber gut microbiota through comparison with sediment microbial communities could lead to the development of more effective probiotics for these endangered species. To characterize sea cucumber gut microbiota and to explore potential contribution of their gut microbiota to the host's ecological roles, we performed a spatiotemporally broad assessment of sea cucumber faecal microbiota and sediment microbiota by 16S rRNA gene sequencing analyses without dissection of specimens (Yamazaki et al ., ). Our results show sea cucumber gut microbiota is shaped by selective enrichment process of ingested microbes from sediments, and the repeated process might transform ambient sediment microbial community structures and promote organic matter mineralization.…”
Section: Introductionmentioning
confidence: 97%